Synthesis of landscape and architecture as a means of expressing national identity - Kashchenko, Tetyana; Akhaimova, Anastasiia; Homon, Olha; Ciepłucha, Wojciech (Landscape Architecture and Art, 2021)
The article raises the issue of interaction between architecture and natural environment in the expression of the people’s national identity. On the examples of different peoples’ cultures means of expression of national color, characteristic landscape receptions are analyzed. The means of national identity expression on the Ukraine territory are studied in detail; the important role of open-air museums in this process is shown. The importance of preserving national identity in the modern conditions of globalization and international architecture is proved. The classical world principles of combining landscape and architecture as expressions of the country national identity are analyzed, as well as the ways of solving this problem in Ukraine by ways of organizing open-air museums, ethnographic corners and fragmentary use of folk motifs in modern parks.